Incidence of rotavirus gastroenteritis by age in African, Asian and European children: Relevance for timing of rotavirus vaccination - Steele, A. Duncan (Hum Vaccin Immunother, 2016)
Variability in rotavirus gastroenteritis (RVGE) epidemiology can influence the optimal vaccination schedule. We evaluated regional trends in the age of RVGE episodes in low- to middle- versus high-income countries in three continents. We undertook a post-hoc analysis based on efficacy trials of a human rotavirus vaccine (HRV; Rotarix™, GSK Vaccines), in which 1348, 1641, and 5250 healthy infants received a placebo in Europe (NCT00140686), Africa (NCT00241644), and Asia (NCT00197210, NCT00329745). Incidence of any/severe RVGE by age at onset was evaluated by active surveillance over the first two years of life. Severity of RVGE episodes was assessed using the Vesikari-scale. The incidence of any RVGE in Africa was higher than in Europe during the first year of life (≤2.78% vs. ≤2.03% per month), but much lower during the second one (≤0.86% versus ≤2.00% per month). The incidence of severe RVGE in Africa was slightly lower than in Europe during the first year of life. Nevertheless, temporal profiles for the incidence of severe RVGE in Africa and Europe during the first (≤1.00% and ≤1.23% per month) and second (≤0.53% and ≤1.13% per month) years of life were similar to those of any RVGE. Any/severe RVGE incidences peaked at younger ages in Africa vs. Europe. In high-income Asian regions, severe RVGE incidence (≤0.31% per month) remained low during the study. The burden of any RVGE was higher earlier in life in children from low- to middle- compared with high-income countries. Differing rotavirus vaccine schedules are likely warranted to maximize protection in different settings.